2016
DOI: 10.1093/ecco-jcc/jjw058
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Differences between Lymphocytic and Collagenous Colitis

Abstract: CC and LC share some regulatory and effector mechanisms, but not others. Higher IL-10 levels and higher Treg and double-negative T cell percentages, found in both CC and LC, could be responsible for the lack of progression of structural damage and the blockade of proinflammatory cytokine production. However, CC and LC are revealed as separate, independent entities, as they show clearly different mucosal lymphocyte profiles, which could be caused by different luminal triggers of the two diseases. Hence, CC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 40 publications
6
35
0
Order By: Relevance
“…''IBD-transformers'' showed remarkably higher expression of tumor necrosis factor (TNF)-a, interferon (IFN)-c, and the Th1-specific transcription factor T-bet as compared with MC-resolved cases [4], all such markers suggestive of a Th1 signature profile. Indeed, other studies demonstrated that IFN-c gene expression correlated with the clinical severity (measured as number of stools per day) of MC patients [13,14]. Those results highlight an interesting issue: MC patients with increased Th1 expression might have a more severe clinical course associated with severe inflammation.…”
Section: Increased Th1 Markers In ''Mc To Ibdtransformers''mentioning
confidence: 84%
See 2 more Smart Citations
“…''IBD-transformers'' showed remarkably higher expression of tumor necrosis factor (TNF)-a, interferon (IFN)-c, and the Th1-specific transcription factor T-bet as compared with MC-resolved cases [4], all such markers suggestive of a Th1 signature profile. Indeed, other studies demonstrated that IFN-c gene expression correlated with the clinical severity (measured as number of stools per day) of MC patients [13,14]. Those results highlight an interesting issue: MC patients with increased Th1 expression might have a more severe clinical course associated with severe inflammation.…”
Section: Increased Th1 Markers In ''Mc To Ibdtransformers''mentioning
confidence: 84%
“…The majority of the studies evaluating the Th1 profile in the MC mucosa are limited to single-staining immunohistochemistry or real-time polymerase chain reaction (PCR) analysis, bulk analyses that do not extend to the single-cell level. In this sense, our reports that measured Th1 and Th17 cells by flow cytometry found that MC patients (both CC and LC subtypes with a mild or benign outcome) had substantially reduced amounts of Th1 and Th17 cells as compared with controls [14] or IBD patients [15], despite increased gene expression of IFN-c and interleukin (IL)-17. Our data suggested that MC is an attenuated form of inflammation, with pro-inflammatory Th1 and Th17 activated at the gene expression levels but blockaded at the protein or cellular level, in a mechanism perhaps mediated by the anti-inflammatory cytokine IL-10 [14].…”
Section: Increased Th1 Markers In ''Mc To Ibdtransformers''mentioning
confidence: 90%
See 1 more Smart Citation
“…Despite its increasing incidence, it is still a relatively rare disease. Importantly, once diagnosis is made there is no formal recommendation to follow-up with new biopsies, and, therefore, it is difficult to get fresh biopsies to pursue molecular studies, and most studies looking at other tissue markers or cytokines in MC, normally rely on a very small number of samples [38] . Here, having access to a large number of samples in several locations among the colon, from more than 30 patients and 30 controls, we were able to describe in detail the expression and gradient of FXR in MC.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, epithelial cells may also play a certain role in the pathogenesis of MC, as they have been implicated in the development of intestinal inflammation [19]. LC and CC may arise from a different immunopathologic basis [20], but the clinical manifestation is mostly common, and therefore it is usually difficult to distinguish one from the other [21]. There are several risk factors that predispose patients to develop MC.…”
Section: Pathophysiology and Risk Factors Of MCmentioning
confidence: 99%